HUMAN DIVERSITY AND EQUALITY - Pratiwi , Ajeng; Annisa, Siti Putri (International Journal of Students Education, 2023)
The Indonesian nation is a multicultural society with its pluralistic nature. Diversity includes differences in culture, religion, race, language, ethnicity, tradition and so on. This article discusses "Human, Diversity and Diversity". Diversity interpreted by conditions in society that have various differences in various fields. Humans are defined as beings who think and reason. Meanwhile, in terms of humans are concepts or ideas that exist in a particular group. Equality comes from the word equivalent or equivalent. The purpose of this writing is to discuss human beings, diversity and equality. The method used is qualitative research. The conclusion of this study is that multicultural life requires multicultural understanding and awareness that respects differences, pluralism and at the same time a willingness to interact fairly with anyone. Facing diversity.